The First Case of Felty’s Syndrome Complicated by COVID-19 Infection - Li Y; Zhu F; Wen R; Hou T; Xie R; Qin J (Dove Medical Press, 2024)
Yueming Li, Fanyou Zhu, Rui Wen, Tingting Hou, Rou Xie, Jiao Qin Department of Rheumatology and Immunology, The Affiliated Changsha Central Hospital, Hengyang Medical School, University of South China, Changsha, Hunan, People's Republic of ChinaCorrespondence: Jiao Qin, Email 2018050712@usc.edu.cnAbstract: Felty's syndrome (FS) is an uncommon disorder with a poor prognosis, and most patients die from infections caused by neutropenia. Currently, there is no standardized treatment strategy, and treatment options are based on case reports and clinical experience. To date, no cases of FS complicated by coronavirus disease-2019 (COVID-19) have been reported. This article reports a successful case of FS complicated by COVID-19. We emphasized treating rheumatic diseases with immunosuppressive therapy at appropriate doses based on strong and effective anti-infection when co-infected.Keywords: Felty's syndrome, rheumatoid arthritis, neutropenia, COVID-19, molnupiravir